Racjonalność pedagogiki – pedagogika racjonalna? - Leppert, Roman (Horyzonty Wychowania, 2009)
The subject of consideration for the author is the question about the rationality of pedagogy, the ways in which it is understood, justification for dealing with this characteristic of pedagogical reflection. The point of departure is understanding rationality as the characteristic of thinking or acting. The criticism that this characteristic has met in the past decades was characterized. Relating rationality to pedagogy understood as natural or discursive knowledge of education (educating and teaching), the premises we refer to when analyzing the problem of rationality of this scientific discipline were presented.